2021
DOI: 10.1002/cjoc.202100401
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyzed Reverse Polarity Oxidative Povarov Reaction of Glycine Derivatives with Maleimides

Abstract: Main observation and conclusion An oxidative tandem (4+2)‐cyclization/aromatization of N‐aryl glycine derivatives with electron‐deficient alkenes was first achieved using Ru(bpy)3Cl2 as a photocatalyst and TBHP as an oxidant in combination with visible‐light irradiation by blue LEDs. One‐electron oxidation and the following α‐deprotonation of glycine derivatives afford α‐amino alkyl radicals, which were then trapped by electrophilic maleimides. As an atom‐economic and efficient method, a variety of pyrrolo[3,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…38 Recently, Bao, Qiu, and Huo's group made a contribution to the reaction of iminium ion intermediates and electron-deficient maleimides. 39 The photocatalyzed activation of N -aryl glycine derivatives and maleimides was achieved in the presence of Ru(bpy) 3 Cl 2 and TBHP. This protocol presented a mild and general method for the synthesis of potentially bioactive pyrrolo[3,4- c ]quinoline-1,3-diones.…”
Section: Intermolecular Cyclization Initiated By Directed C(sp3)–h Ox...mentioning
confidence: 99%
“…38 Recently, Bao, Qiu, and Huo's group made a contribution to the reaction of iminium ion intermediates and electron-deficient maleimides. 39 The photocatalyzed activation of N -aryl glycine derivatives and maleimides was achieved in the presence of Ru(bpy) 3 Cl 2 and TBHP. This protocol presented a mild and general method for the synthesis of potentially bioactive pyrrolo[3,4- c ]quinoline-1,3-diones.…”
Section: Intermolecular Cyclization Initiated By Directed C(sp3)–h Ox...mentioning
confidence: 99%
“…As an efficient merger of photoredox catalysis (PRC) and synthetic organic electrochemistry (SOE), synthetic photoelectrochemistry (PEC) has been illustrated as a sustainable synthetic platform for novel transformations in organic synthesis over the past decade. Featuring a wide redox window (−4.5 to 4.5 eV), mild conditions, “traceless” redox agents, and energy saving, PEC is deemed as a new frontier for single electron transfer (SET) and used as a combined “upconversion” technology for the energy transfer from photons and electrons to reactants. A key issue for PEC is the exploitation and selection of photoelectrocatalysts with their redox and photophysical properties to precisely match the reactants. Despite the fact that a series of photo-responsive redox mediators including cyclopropenium ions, triarylamines, naphthalene-imides, and some other aromatics were developed (Figure ), metal-based ones are often being ignored and rarely reported in PEC. In fact, benefiting from versatile properties including ligand-to-metal charge transfer (LMCT), metal-to-ligand charge transfer (MLCT), and proton-coupled electron transfer (PCET), metal-based catalysts have been widely used in SET chemistry. , …”
Section: Introductionmentioning
confidence: 99%
“…25−27 In fact, benefiting from versatile properties including ligand-to-metal charge transfer (LMCT), 28−30 metal-to-ligand charge transfer (MLCT), 3 1 and proton-coupled electron transfer (PCET), 32−34 metal-based catalysts have been widely used in SET chemistry. 35,36 With the advantages of reversible Ce III /Ce IV redox pairs, cerium salts have been investigated in the fields of catalytic organic synthesis. 30,37−48 Notably, it was found that cerium-(IV) showed excellent LMCT properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A series of visible-light-assisted C­(sp 3 )–H activations of arylglycine derivatives have been demonstrated . In addition to the prevalent dehydrogenative coupling reactions, to the best of our knowledge, another direct site-specific functionalization of glycine derivatives has been rare to date . In addition, just like most traditional organic reactions, a suitable photocatalyst is usually required to activate the substrates to produce the desired products even under visible-light irradiation …”
mentioning
confidence: 99%
“…Ethyl-4-(2-fluorophenyl)-2-[(4-methoxyphenyl)amino]-4-oxobutanoate (3ac). The general procedure afforded a yellow solid: isolated yield 22.5 mg, 65% yield; mp 56.4−56.8 °C (5:1 PE/EA); 1 H NMR (400 MHz, CDCl 3 ) δ 7.87 (td, J = 7.6, 1.9 Hz, 1H), 7.52 (m, 1H), 7.23 (m, 1H), 7.13 (m, 1H), 6.77 (d, J = 9.0 Hz, 2H), 6.68 (d, J = 8.9 Hz, 2H), 4.50 (t, J = 5.4 Hz, 1H), 4.25 (s, 1H), 4.18 (q, J = 7.1 Hz, 2H), 3.73 (s, 3H), 3.54 (m, 2H), 1.21 (t, J = 7.1 Hz, 3H); 13 C{ 1 H} NMR (101 MHz, CDCl 3 ) δ 195.6 (d, J = 4.0 Hz), 173.3, 163.5, 161.0, 153.1, 140.8, 135.2 (d, J = 9.1 Hz), 130.8 (d, J = 2.4 Hz), 124.7 (d,J = 3.3 Hz),116.8 (d,J = 23.7 Hz),115.8,114.9,61.5,55.8,54.5 (d,J = 2.4 Ethyl-2-[(4-methoxyphenyl)amino]-4-oxo-4-(m-tolyl)butanoate (3ad). The general procedure afforded a reddish brown solid: isolated yield 24.9 mg, 73% yield; mp 80.9−81.4 °C (5:1 PE/EA); 1 H NMR (400 MHz, CDCl 3 ) δ 7.76−7.71 (m, 2H), 7.40−7.32 (m, 2H), 6.77 (d, J = 9.0 Hz, 2H), 6.68 (d, J = 9.0 Hz, 2H), 4.53 (t, J = 5.4 Hz, 1H), 4.23 (s, 1H), 4.18 (q, J = 7.1 Hz, 2H), 3.73 (s, 3H), 3.51 (d, J = 5.5 Hz, 2H), 2.40 (s, 3H), 1.20 (t, J = 7.1 Hz, 3H); 13 C{ 1 H} NMR (101 MHz, CDCl 3 ) δ 197.…”
mentioning
confidence: 99%